Fundamental concepts of law - Bozbayındır, Ali Emrah (Anadolu Üniversitesi, 2017)
Introduction, What is Law?, The Functions Of Law, Legal Traditions, The Sources Of Law: Where Does Law Come, From?, Law And Morality -- INTRODUCTION: This is an introductory chapter which will familiarize the students with basic concepts and functions of law. On doing so, the chapter first provides answers to the question of what is law and how it functions. The chapter aims to provide an insight into the nature and function of law. After analysing the concept of law and its functions the chapter shall provide information about the most important living legal traditions in the world. What the common law and civil traditions are and how they evolved will be one of the main themes of the chapter. After introducing roots and basic concepts of these traditions, the chapter will provide you information about principle sources of law and the means by which laws are made. Overall, after studying this chapter you should understand the following main points: • The concept and functions of law • The most important legal traditions in the world • The development of common law and civil law traditions • Principal sources of law with an emphasis on Turkish law
T.C. ANADOLU UNIVERSITY PUBLICATION NO: 3598 -- FACULTY OF OPEN EDUCATION PUBLICATION NO: 2429 -- E-ISBN: 978-975-06-2417-9
Keywords: Definition of law; Functions of law; Justice; Order; Legal traditions; Civil law; Common law; Religious law; Sources of law; Hierarchy of laws in Turkey